Diffuse soil gas emissions of gaseous elemental mercury (GEM) from hydrothermal-volcanic systems: An innovative approach by using the static closed-chamber method. (March 2016) - Tassi, F.; Cabassi, J.; Calabrese, S.; Nisi, B.; Venturi, S.; Capecchiacci, F.; Giannini, L.; Vaselli, O.
Abstract: This study was aimed to test a new methodological approach to carry out measurements of gaseous elemental mercury (GEM) diffusively emitted from soils in hydrothermal-volcanic environments. This method was based on the use of a static closed-chamber (SCC) in combination with a Lumex ® RA-915M analyzer that provides GEM measurements in a wide range of concentrations (from 2 to 50, 000 ng m −3 ). Gas samples were collected at fixed time intervals from the SCC positioned on the ground (time-series samples). The Lumex ® inlet port was equipped with a three-way Teflon valve allowing the free entrance of air through a carbon trap, in order to: (i) prevent disturbance to the Lumex ® operative flow rate (10 L min −1 ) during the injection of the gas samples from the SCC and (ii) minimize the instability of the baseline signal induced by possible variations of GEM concentrations in air. In the lab, known amounts of GEM, pipetted from a vessel containing an Hg-saturated air in equilibrium with liquid mercury at 27 °C, were injected in the Lumex ® via the modified inlet port to construct a calibration curve. The latter was used to calculate the amount of GEM in the SCC (KSCC ) from the corresponding GEM concentrations measured by the Lumex ® analyzer. The KSCC values of the time-series samples were proportionally increasing with the GEM fluxes (ϕGEM), thus ϕGEM values were computed according to the following equation: ϕGEM = (dKSCC /dt)/A, where A is the basal area of the SCC and dt is the time interval of the time-series sampling. Up to 214 ϕGEM measurements were carried out at Solfatara crater (Campi Flegrei, southern Italy), a hydrothermally altered tuff cone characterized by an anomalous diffuse soil emission of GEM-rich geogenic gases. The measured ϕGEM values varied up to 4 orders of magnitude, from 1, 296, corresponding to the sensitivity of the method at the selected sampling time interval (1 min), to 1, 957, 500 ng m −2 day −1, and were consistent with those recently measured in this crater using a different method. In the field, 10 replicates were carried out in 5 selected sites, allowing to demonstrate that the proposed method has a high reproducibility (RDS < 4%). The ϕGEM and ϕCO2 values, the latter being measured in the same 214 sites by using the accumulation chamber method, showed a low correlation, although both gases were originated from the same deep source. This suggests that GEM and CO2 soil fluxes are differently affected by environmental parameters, such as soil humidity and temperature, which have a strong effect on the release of GEM from the soil, whereas they do not play a significant role in the diffuse degassing of CO2 . The measured fluxes were used to compute the CO2 and GEM total outputs (402 and 5.41 × 10 −6 t day −1, respectively) from the study area (92, 000 m 2 ) and to construct contour maps showing the spatial distribution of the ϕCO2 and ϕGEM values. By modifying the geometry of SCC and the time interval of the sampling series, the proposed method can be applied to the measurements of GEM soil fluxes in other geological systems and man-made environments. Highlights: A new method to estimate soil diffuse gaseous elemental mercury (GEM) is presented. This approach combines the static closed chamber method and Lumex® RA-915M. Up to 214 GEM flux measurements were carried at Solfatara Crater (Italy). The measured ϕGEM values were between 1296 and 1, 957, 500 ng m −2 day −1 . The total output of GEM in the study area was of 5.41.10 −6 tons/day